Teachers' Adjustment as a Mediator Between Occupational Stress and Psychological Well-Being - Kumari, Madhumita; Singh, Lav Kumar (Journal of Neonatal Surgery, 2025)
The present study investigated the mediating role of teachers' adjustment in the relationship between occupational stress and psychological well-being among school teachers. A descriptive, correlational, and mediation research design was employed. The sample comprised 300 teachers selected from government and private secondary and senior secondary schools of Darbhanga district, Bihar, through a purposive-cum-incidental sampling technique. Occupational stress was assessed using the Occupational Stress Index (OSI) developed by A. K. Shrivastava and A. P. Singh, psychological well-being was measured using the Psychological Well-Being Scale (PWBS) developed by Devendra Singh Sisodia and Pooja Choudhary, and adjustment was assessed using the Mangal Teacher Adjustment Inventory (MTAI) developed by S. K. Mangal. Data were analyzed using descriptive statistics, Pearson's product-moment correlation, and mediation analysis through Hayes' PROCESS Macro (Model 4). The findings revealed that occupational stress was significantly and negatively associated with psychological well-being, while poorer adjustment was also related to lower psychological well-being. Occupational stress showed a significant positive association with poor adjustment. Mediation analysis indicated that adjustment partially mediated the relationship between occupational stress and psychological well-being, suggesting that occupational stress affects teachers' well-being both directly and indirectly through its influence on adjustment. The study highlights the importance of strengthening teachers' adjustment capacities alongside reducing occupational stress to promote psychological well-being and improve professional effectiveness in educational settings...